HUKUM PERKAWINAN ADAT DI INDONESIA: KONFLIK ANTARA LEGITIMASI SOSIAL DAN LEGALITAS FORMAL (STUDI KASUS MAMASA) - Dwi Desi Yayi Tarina; Arum Agustin Arviani; Keizaraya Umaiza; Ratu Sandiva (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Customary marriage law is part of the living law in Indonesian society that regulates social relationships, kinship systems, and family structures. In practice, customary marriages are often considered valid because they have fulfilled customary provisions and gained community recognition. However, problems arise when such marriages are not registered in accordance with Law Number 1 of 1974 concerning Marriage. This study aims to analyze the conflict between Mamasa customary law and national law, including the practice of underage marriage and its legal consequences, using a normative juridical method through a conceptual approach and a case approach. The results show that Mamasa customary marriages have strong social legitimacy, but are not always followed by official registration, and underage marriage practices are still found. This condition creates a conflict, resulting in legal uncertainty, particularly regarding marital status, the position of children, and the protection of women. Therefore, harmonization between customary law and national law is necessary to ensure legal certainty and protection.